Application of Potential and Vortex Fields to the Description of Gravitation and Electromagnetism - Ivanchenko, V. M. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We propose a system of differential equations in the tensor general-covariant form whose solutions are called gravitational and charged particles. For free fields, solutions are found in the form of Newton and Coulomb potentials. For a particle that rotates with constant velocity around another particle with large mass, a solution is obtained in the form \(ω = k\sqrt {\frac{{m_2 }}{{R^3 }}} \) if the particle is uncharged, and in the form \(ω = k\sqrt {\frac{{ε _1 ε _2 }}{{m_1 R^3 }}} \) if it is charged.